A Contextual Artificial Intelligence Ecosystem Framework for STIT Bustanul Ulum: A Multisite Comparative Study of the Zawia University and Badakhshan University - Andrianto, Dedi; Rohman, Syaifur; Sari, Siska Difita (Scidac Plus, 2025)
The rapid diffusion of artificial intelligence (AI) in higher education presents significant governance challenges, particularly in institutions operating within distinct ethical and cultural contexts. However, existing AI governance models remain largely technocratic and insufficiently responsive to local institutional realities. This study aims to develop a contextually grounded and policy-relevant Artificial Intelligence Ecosystem Framework tailored to Islamic higher education institutions. Employing a qualitative multisite comparative design, the research was conducted at STIT Bustanul Ulum (Indonesia), the Zawia University (Libya), and Badakhshan University (Afghanistan). Data were collected through semi-structured interviews, institutional observations, and document analysis, and were analyzed using cross-case thematic comparison. The findings reveal that effective AI adoption is not determined solely by technological capacity but by coordinated institutional readiness across five interdependent dimensions: digital infrastructure, human resource competence, adaptive institutional policy, ethical orientation, and collaborative sustainability networks. The study further demonstrates that within Islamic higher education, ethical and religious values function as internal regulatory mechanisms that promote responsible AI governance rather than inhibit innovation. The proposed AI Ecosystem Framework offers a holistic governance model that integrates technological advancement with contextual, ethical, and institutional considerations, contributing both theoretically to AI governance discourse and practically to policy development in faith-based higher education settings.